2013
DOI: 10.1159/000348504
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-23b Inhibits Enterovirus 71 Replication through Downregulation of EV71 VPl Protein

Abstract: Enterovirus 71 (EV71) is one of the causative pathogens of hand-foot-and-mouth disease and effective antiviral agents and vaccines against this virus have, to date, not been available. MicroRNAs (miRNAs) are a recently discovered class of RNAs with the function of post-transcriptional gene expression regulation. It has been demonstrated that miRNAs play important roles in the complicated interaction network between virus and host, while few studies have explored the role of miRNAs in EV71 infection. A recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 27 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…5b). The expression pattern determined by miRNA sequencing was confirmed by taqman RT-qPCR for 2 miRNAs that were described in the literature to be related to enteroviral infection: miR-146a-5p (upregulated) and miR-23b (downregulated) [45][46][47][48] ( Fig. 5c-d).…”
Section: Pattern Of Cellular Mirnas In Ductal-like Cells Persistentlysupporting
confidence: 53%
“…5b). The expression pattern determined by miRNA sequencing was confirmed by taqman RT-qPCR for 2 miRNAs that were described in the literature to be related to enteroviral infection: miR-146a-5p (upregulated) and miR-23b (downregulated) [45][46][47][48] ( Fig. 5c-d).…”
Section: Pattern Of Cellular Mirnas In Ductal-like Cells Persistentlysupporting
confidence: 53%
“…[34][35][36] Whereas to date no data on human CVB3 infections were available, several miRs influenced enterovirus replication in cell and animal models. miR-23b 37 and miR-296-5p (suppressed in CVB3-PERS) inhibit enterovirus 71 replication. 38 miR-23b, and miR-146b, 45 but none of these miRs were differentially expressed in CVB3-ELIM versus CVB3-PERS.…”
Section: Possible Origins Of Differential Mir Expression In Patients mentioning
confidence: 99%
“…On the one hand, host miRNAs may target the viral genome directly to suppress viral replication. Wen et al [35] have reported that miRNA-23b expression is downregulated by EV71 infection and that this miRNA inhibits viral replication via suppression of the structural protein VP1. In addition, Zheng et al [36] have reported that hsa-miR-295-5p expression is upregulated by EV71 infection and that this miRNA suppresses viral replication by targeting the VP1 and VP3 coding regions.…”
Section: Discussionmentioning
confidence: 99%